HUBUNGAN PELAKSANAAN KELUARGA SADAR GIZI (KADARZI) DENGAN STATUS GIZI ANAK 1-4 TAHUN - Hardika, Mufida Dian (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Relationship of Implementation of Family Conscious Nutrition (KADARZI) With Child Nutrition Status 1-4 Years. Nutritional status of children is influenced by several factors one of which is the nutritious family conscious behavior, KADARZI family will do regular weighing of the child. The Survey result data in bangunsari Region on february 2017 from 136 children (1-4 years old) found 11 child (19 %) with under nutrition state. Alot of them caused not doing good nutrition of family behaviour their not measured the weight of their children regularly in the integrated service post. Based in the reality above, the objective purpose  of this study was to known the corellation between good nutrition of family behaviour with nutrition State at children  (1-4 years old) in bangunsari region of Madiun Regency. This research analize used analitic method cross sectional with sample amount 58 mother and their child which taken with simple random sampling method. Variable of doing good nutrition of family behaviour measured with Questionaire, and variable of child nutrition state    measured with observation weight of child. The data analize was using the statistical of kendall tau. Based of the study result on April-Mei 2017 in bangunsari region, variable of doing good nutrition of family behaviour found alot of them 36 (62,1 %) good nutrition behaviour. And variable  nutrition state found  alot of them 49 child (84,5%) with good nutrition state. Based to analized the r value of kendall tau statistic are 0,0441 and probability (P) value= 0,001 < α=0,05, there are any significant corellation between Variable of  good nutrition of family behaviour, and variable of child  nutrition state. proposed that  mother have children to more care the good nutrition behaviour  for the chidreen  to prevent incident of under and bad nutrition state in children. Keywords: Good nutrition of family behavior, Nutrition state